Comparison of 2 Weight-Based Heparin Dosing Nomograms in Neurology and Vascular Surgical Patients. Issue 1 (February 2015) - Marotti, Sally B.; Barras, Michael; Kirkpatrick, Carl
Abstract : Background: Unfractionated heparin sodium (UFH) is used in neurology and vascular surgical patients to treat and prevent thromboembolic occlusions and requires weight-based dosing to achieve a therapeutic range; however, the optimal dosing strategy is not known. This study sought to determine whether an intravenous (IV) weight-based UFH dosing nomogram based on an 80-unit/kg bolus and 18-unit·kg −1 ·h −1 initial infusion rate achieves therapeutic anticoagulation [activated partial thromboplastin time (aPTT), 65–110 seconds] more rapidly than that based on a 60-unit/kg bolus and 12-unit·kg −1 ·h −1 initial infusion rate in 98 neurology and vascular surgery patients. Methods: The study consisted of a retrospective chart review of adults prescribed and administered IV UFH for >6 hours, admitted under the neurology or vascular surgery teams and administered UFH for transient ischemic attack, stroke, acute ischemic limb, or postoperative revascularization. Results: The time to therapeutic aPTT analysis showed superiority of the higher dose ( P = 0.04, log-rank test). At 6 hours, there was a significantly greater proportion of patients within the therapeutic range in the higher dose group (36.0% versus 16.7%, P = 0.03), with fewer subtherapeutic aPTTs (34.0% versus 70.8%, P < 0.001) and more supratherapeutic aPTTs (30.0% versus 12.5%, P = 0.034). Conclusions: A weight-based nomogram for IV UFH using an 80-unit/kg bolus and an initial infusion rate of 18 units·kg −1 ·h −1 showed a more rapid achievement of therapeutic aPTT when compared with a 60:12 dosing nomogram. Future research assessing a 70-unit/kg bolus dose is recommended.